A Shear‐Thinning, Self‐Healing, Dual‐Cross Linked Hydrogel Based on Gelatin/Vanillin/Fe3+/AGP‐AgNPs: Synthesis, Antibacterial, and Wound‐Healing Assessment - Chanon Talodthaisong; Rina Patramanon; Saengrawee Thammawithan; Sarawut Lapmanee; Lamai Maikaeo; Phitchan Sricharoen; Mattaka Khongkow; Katawut Namdee; Angkana Jantimaporn; Navaphun Kayunkid; James A. Hutchison; Sirinan Kulchat (Macromolecular Bioscience, 2023)
as dual crosslinking agents. Rheological studies indicate the formation of a strong gel found to be injectable and exhibit rapid self-healing (within 10 min). The hydrogels also exhibited a high degree of swelling, suggesting potential as wound dressings since the absorption of large amounts of wound exudate, and optimum moisture levels, lead to accelerated wound healing. Andrographolide, an anti-inflammatory natural product is used to fabricate silver nanoparticles, which are characterized and composited with the fabricated hydrogels to imbue them with anti-microbial activity. The nanoparticle/hydrogel composites exhibit activity against Escherichia coli, Staphylococcus aureus, and Burkholderia pseudomallei, the pathogen that causes melioidosis, a serious but neglected disease affecting southeast Asia and northern Australia. Finally, the nanoparticle/hydrogel composites are shown to enhance wound closure in animal models compared to the hydrogel alone, confirming that these hydrogel composites hold great potential in the biomedical field.
Keywords: Phytochemistry and biological activities of Ficus species